PENGUNAAN WEB PENDIDIKAN UNTUK MENGEMBANGKAN MODEL PEMBELAJARAN INTERAKTIF MENGGUNAKAN PLATFROM EDUCAPLAY & WORDWALL - Hidayat Muharam; Nur Hikmah (Journal of Community Services on Multidisciplinary Sciences, 2025)
The digital era does indeed require broader integration of technology in the field of education. However, to date, most teachers at SMKN 1 Gorontalo have not yet engaged in activities on interactive web platforms such as Educaplay and Wordwall. This community project aims to inform and educate teachers about these platforms, ultimately enabling them to create engaging and interactive learning materials. The methods include practical training and guidance in creating quizzes, educational games, and interactive exercises. As a result, teachers can design independent learning materials, increase student participation, and create an innovative atmosphere. This intervention stems from the same positive spirit of implementing the Merdeka Belajar Curriculum to equip teachers and students with digital literacy.